Modelling analysis of dietary behaviors and oral health status to assess the impact on the mental well-being of elderly individuals: a cross-sectional survey study - Huang, Chan; Song, Mingzhu; Wei, Xiao; Wang, Xingyan; Dai, Honglin; Gou, Zhiqiong; Chenwu, Feiyang; Jiang, Yanqiu; Wan, Jie; Guo, Yurun; Yu, Xiaoping (Frontiers in Nutrition, 2025)
Background and objectiveGlobal aging is becoming a pressing concern, with a heightened focus on the mental well-being of the elderly population. The mental health of the elderly is influenced by a plethora of factors such as physical health, social support, lifestyle, and psychological aspects. This study investigates the influence of oral health and eating behaviors on depression, anxiety, and dementia in elderly individuals aged 65 and older in China. The aim is to determine the effect sizes of these factors and establish a foundation for implementing tailored intervention strategies.Study design and methodsThe cross-sectional survey study employed data from the 2020 follow-up of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) released in April 2020. The study included a cohort of 3,188 eligible older adults. Seven aspects of oral health were assessed, encompassing the evaluation of the number of teeth, dental restorations, tooth brushing habits, occurrence of tooth pain, as well as cheek or jaw pain. Additionally, 17 items pertaining to eating behaviors were examined, covering dietary aspects such as staple foods, vegetables, fruits, tastes, and the use of cooking oils. The study assessed depression and sleep through 11 items, with higher scores reflecting a predisposition toward depression. A scoring threshold of over 27 identified individuals in the group prone to depression. Anxiety levels were assessed through seven items, where higher scores denoted a predisposition toward anxiety. Participants scoring above 0 were categorized into the anxiety-prone group. Cognitive function was assessed through seven items, with higher scores suggestive of a propensity toward dementia. Participants with scores exceeding 8 were categorized into the dementia-prone group. Rank-sum tests and chi-square tests were employed for the univariate analysis of variations in depression, anxiety, and dementia among elderly individuals with varying oral health and eating behaviors. Variables demonstrating statistical significance in the univariate analysis were further examined in logistic regression analysis.ResultsThis study uncovered a correlation between the oral health and dietary behaviors of middle-aged and elderly individuals and their vulnerability to depression, anxiety, and dementia. Our findings showed that about 7.62% of middle-aged and elderly individuals in China were prone to depression. Meanwhile, around 49% of this population had inadequate teeth to chew and digest properly, and nearly 10% lacked dental restorations. Elderly individuals who had dental surgery had a 50% lower risk of depression compared to those who did not (OR = 0.58). Additionally, 36.7% of this group were prone to anxiety, and 7.53% were at risk of developing dementia. Elderly individuals who brushed their teeth at least twice a day and maintained oral hygiene were less likely to develop anxiety and dementia, with odds ratios of 0.72 and 0.78, respectively. This study conducted in China revealed that among individuals aged 65 and older, 22% reported experiencing tooth pain, while 11% reported experiencing cheek or jaw pain. Controlling tooth, cheek, or jaw pain significantly diminished the likelihood of anxiety in elderly population, with odds ratios of 0.79 and 0.69, respectively. The study also uncovered that consuming an adequate amount of fresh vegetables on a daily basis was highly advantageous in preserving the mental well-being of elderly individuals, and might reduce the risk of depression by 32.5%, anxiety by 50.3%, and dementia by 50%. Elderly individuals could potentially prevent anxiety and dementia by consuming an adequate amount of fruits daily. Conversely, a diet high in salt and spice was potentially associated with an increased risk of anxiety in this population. Furthermore, middle-aged elderly individuals (under 80) exhibited a potentially higher susceptibility to anxiety compared to older elderly individuals (aged 80 and above).ConclusionAn immediate imperative exists to enhance oral health education, elevate oral hygiene standards, and guarantee prompt dental restoration among middle-aged and elderly populations in order to mitigate their susceptibility to depression, anxiety, and dementia. Safeguarding the mental health of elderly individuals necessitates the coordination of diverse disciplines, encompassing dentistry, nutrition, and public health expertise.